CircRNA-006258 Sponge-Adsorbs miR-574-5p to Regulate Cell Growth and Milk Synthesis via EVI5L in Goat Mammary Epithelial Cells - Zhang, Meng (Genes (Basel), 2020)
The development of the udder and the milk yield are closely related to the number and vitality of mammary epithelial cells. Many previous studies have proved that non-coding RNAs (ncRNAs) are widely involved in mammary gland development and the physiological activities of lactation. Our laboratory previous sequencing data revealed that miR-574-5p was differentially expressed during the colostrum and peak lactation stages, while the molecular mechanism of the regulatory effect of miR-574-5p on goat mammary epithelial cells (GMECs) is unclear. In this study, the targeting relationship was detected between miR-574-5p or ecotropic viral integration site 5-like (EVI5L) and circRNA-006258. The results declared that miR-574-5p induced the down-regulation of EVI5L expression at both the mRNA and protein levels, while circRNA-006258 relieved the inhibitory effect through adsorbing miR-574-5p. EVI5L blocked the G1 phase and promoted the S phase by activating the Rab23/ITGB1/TIAM1/Rac1-TGF-β/Smad pathway in GMECs. By increasing the protein expression of Bcl2 and reducing the protein expression of Bax, EVI5L promoted cell growth and inhibited apoptosis. The activation of the PI3K/AKT–mTOR signaling pathway promoted the production of triacylglycerol (TAG) and β-casein in GMECs. The circRNA–006258/miR-574-5p/EVI5L axis could regulate the cell growth and milk synthesis of GMECs by sponge-adsorbed miR-574-5p. These results would provide scientific evidence for precision animal breeding in the industry of dairy goats.